2010
DOI: 10.1128/aac.01045-09
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Quinolone Resistance in Vibrio cholerae

Abstract: Ciprofloxacin was introduced for treatment of patients with cholera in Bangladesh because of resistance to other agents, but its utility has been compromised by the decreasing ciprofloxacin susceptibility of Vibrio cholerae over time. We correlated levels of susceptibility and temporal patterns with the occurrence of mutation in gyrA, which encodes a subunit of DNA gyrase, followed by mutation in parC, which encodes a subunit of DNA topoisomerase IV. We found that ciprofloxacin activity was more recently furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 28 publications
4
41
1
1
Order By: Relevance
“…The qnrVC gene from Vibrio cholerae can also be located in a plasmid (30) or in transmissible form as part of an integrating conjugative element (23). These qnr genes generally differ in sequence by 30% or more from qnrA and each other.…”
mentioning
confidence: 99%
“…The qnrVC gene from Vibrio cholerae can also be located in a plasmid (30) or in transmissible form as part of an integrating conjugative element (23). These qnr genes generally differ in sequence by 30% or more from qnrA and each other.…”
mentioning
confidence: 99%
“…Interestingly, P qnrVC had been found in qnrVC2, qnrVC3, and qnrVC4 (4,7,14). The 5= UTRs of these alleles are very similar in sequence and length to that of qnrVC1.…”
mentioning
confidence: 81%
“…First, it was found in a typical class 1 integron (2). Kim et al (3) verified this cassette in an integrated conjugative element (ICE) embedded in the chromosome. Comparing the two results, it can be concluded that this high mobility increases the chance of qnrVC spread, not only among V. cholerae strains.…”
Section: Spread Of the Qnrvc Quinolone Resistance Determinant In Vibrmentioning
confidence: 99%